Un grafito tartesio hallado en el yacimiento del Castillo de Doña Blanca (Puerto de Sta. María, Cádiz) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A Tartesian inscription (on a fragment of Phoenician Red-slip ware) was found on the site of Castillo de Doña Blanca (Puerto de Sta. María, Cadiz), together with a numerous group of Phoenician grafitti. The Tartesian inscription presents two complete signs (and minimal remains of anothertwo possible letters). It could be read as ]tute[ o ]tetu[. The archaeological datation of the piece (first half / mid VII century B. C.) is the oldest known to date piece of evidence of Tartesian writing.
Keywords: Epigraphy; Iberian Peninsula; Tartesian; Phoenician; Grafitti; Writings